Sentiment Analysis of Local Sunscreen Skintific, Somethinc, and Avoskin with Naive Bayes and SVM - Clarisha, Windi; Fani, A. Astri Merilsa; Surianto, Dewi Fatmarani; Fadilah, Nur (Jambura Journal of Electrical and Electronics Engineering, 2025)
Indonesia’s beauty industry, particularly local sunscreen products, has experienced rapid growth alongside increasing public awareness of the importance of skin protection against ultraviolet rays. Consumer reviews on digital platforms have become a vital source of information to understand user perceptions and preferences. This study aims to analyze sentiment toward three local sunscreen brands—Skintific, Somethinc, and Avoskin—by comparing two text classification methods: Naïve Bayes and Support Vector Machine (SVM). To address the imbalance in the number of positive and negative sentiment data, the Synthetic Minority Over-sampling Technique (SMOTE) was applied. The results show that applying SMOTE to Naïve Bayes significantly improved the accuracy from 81% to 93%, along with notable enhancements in precision, recall, and F1-score. Conversely, applying SMOTE to SVM slightly reduced accuracy from 92% to 91%, although the performance for positive sentiment remained stable. These findings indicate that the combination of Naïve Bayes and SMOTE is more effective in handling imbalanced data for sentiment analysis of beauty products. The implications of this study can serve as a basis for decision-making in product development and marketing strategies within the beauty industry, particularly in aligning with consumer sentiment.Industri kecantikan Indonesia, khususnya produk sunscreen lokal, menunjukkan pertumbuhan pesat seiring meningkatnya kesadaran masyarakat akan pentingnya perlindungan kulit dari sinar ultraviolet. Ulasan konsumen di platform digital menjadi sumber informasi penting untuk memahami persepsi dan preferensi pengguna. Penelitian ini bertujuan untuk menganalisis sentimen terhadap tiga merek sunscreen lokal—Skintific, Somethinc, dan Avoskin—dengan membandingkan dua metode klasifikasi teks, yaitu Naïve Bayes dan Support Vector Machine (SVM). Untuk mengatasi ketidakseimbangan jumlah data antara sentimen positif dan negatif, digunakan teknik Synthetic Minority Over-sampling Technique (SMOTE). Hasil menunjukkan bahwa penerapan SMOTE pada Naïve Bayes meningkatkan akurasi dari 81% menjadi 93%, serta memperbaiki precision, recall, dan F1-score secara signifikan. Sebaliknya, penerapan SMOTE pada SVM justru sedikit menurunkan akurasi dari 92% menjadi 91%, meskipun performa untuk kategori sentimen positif tetap stabil. Temuan ini menunjukkan bahwa kombinasi Naïve Bayes dengan SMOTE lebih efektif dalam menangani data tidak seimbang untuk analisis sentimen produk kecantikan. Implikasi dari penelitian ini dapat digunakan oleh pelaku industri kecantikan sebagai dasar pengambilan keputusan dalam pengembangan dan pemasaran produk berbasis persepsi konsumen.